Cryopreservation of Unrelated Hematopoietic Stem Cells from a Blood and Marrow Donor Bank During the COVID-19 Pandemic: A Nationwide Survey by the Japan Marrow Donor Program - Kanda, Yoshinobu (Transplant Cell Ther, 2021)
During the COVID-19 pandemic, donor hematopoietic stem cell grafts are frequently cryopreserved to ensure the availability of graft before starting a conditioning regimen. However, the safety of cryopreservation has been controversial in unrelated hematopoietic stem cell transplantation (HSCT), especially for bone marrow (BM) grafts. In addition, in unrelated HSCT, the effect of the time from harvest to cryopreservation of donor grafts required for the transportation of donor graft has not been fully clarified. In this study, we retrospectively analyzed the first 112 patients with available data who underwent cryopreserved unrelated blood and marrow transplantation through the Japan Marrow Donor Program during the COVID-19 pandemic. There were 112 patients, including 83 who received BM grafts and 29 who received peripheral blood stem cell (PBSC) grafts. The median time from stem cell harvest to cryopreservation was 9.9 hours (range, 2.6 to 44.0 hours), and the median time from cryopreservation to infusion was 231.2 hours. The incidence of neutrophil engraftment at day 28 after HSCT was 91.1%, and among 109 patients (excluding 3 patients with early death), all but 1 patient achieved neutrophil engraftment within 60 days after HSCT. The time to neutrophil engraftment and time to platelet engraftment were shorter in PBSC transplantation compared with BM transplantation (BMT), but the differences were not statistically significant (P = .064 and .18). Multivariate analysis among BM recipients revealed that a higher number of frozen nucleated cells and the absence of HLA mismatch were associated with faster neutrophil engraftment. The time to neutrophil engraftment after unrelated cryopreserved BMT was not different from that after unrelated BMT without cryopreservation. Our findings suggest that unrelated donor BM and PBSC grafts can be safely cryopreserved even after transit from the harvest center to the transplantation center. In the current COVID-19 pandemic, cryopreservation can be considered as an option while balancing the risks and benefits of the procedure.